Læring og kompetanseutvikling i kommunehelsetenesta - ein intervjustudie av kreftsjukepleiarar - Astrid Bjørnerheim Hynne; Marit Kvangarsnes (Septentrio Academic Publishing, 2015)
Learning and competence development in community health service - an interview study of cancer nurses The number of cancer patients is expected to increase 30% by 2020. To meet the needs of seriously ill and dying cancer patients the community health service must be strengthened. There is little knowledge about the development of competence in the community health service. The aim of this study was to get more knowledge about competence development of cancer nurses.The study has a phenomenological hermeneutical design. Data was based on eight qualitative interviews with cancer nurses. The content of daily work and the cooperation within the community of practice were found to be important. Experience, theoretical knowledge, expectations and attitudes were of importance in their learning, and this is accomplished in cooperation with others through trust, having enough time and responsibility. It will be a challenge to meet the demands to quality and competence in future cancer care. Employing advanced nurse practitioners can be a resource, strengthening quality, improving nursing and innovation.